From the mind to under the skin: integrating endocrine measures into organizational and behavioral research - Accetta, Rodrigo Furst de Freitas (2018)
Scholars aiming at developing a more comprehensive and integrated understanding of workplace and social phenomena have taken a keen interest in the incorporation of biological processes into organizational and behavioral research. This work seeks to introduce organizational and behavioral scholars to the basic aspects of research involving physiological data collection, with the aim at both describing in detail specific procedural protocols as well as facilitating the application and comprehension of this method. Specifically, in this paper, we focus on two endocrine markers that account for hormonal responses, namely cortisol and testosterone. We first review empirical literature measuring at least one of the endocrine measures of inquiry and then discuss both methodological and conceptual patterns inherent in this kind of research. More importantly, besides elaborating upon the methodological advantages, as the shortcomings associated with the measurement of these endocrine indicators, we offer a practical description of standard research protocols involved in studies that incorporate measures of either cortisol or testosterone. On the pretense of supporting scholars become better acquainted with the method and its procedures, we conclude by presenting an empirical example in which we illustrate how to measure endocrine activity in an actual research setting.